The Influence of Payment System Digitalization on Consumer Transaction Efficiency in Urban Areas - Ummy Kalsum; Abdul Wakil (Nomico, 2025)
This study investigates the impact of digital payment system adoption on transaction efficiency among urban consumers in Indonesia. As digital technology increasingly penetrates the financial sector, particularly through e-wallets, QR code systems, and mobile banking, there is a growing need to assess how such tools enhance the effectiveness and convenience of daily consumer transactions. The research employed a quantitative approach using a structured questionnaire distributed to 120 respondents residing in urban areas. Data analysis was conducted using SPSS, including validity and reliability tests, normality testing, and simple linear regression. The results reveal a strong and statistically significant positive relationship between digital payment adoption and transaction efficiency. Respondents reported that digital payment systems improved transaction speed, reduced the need for physical cash, and offered better tracking of financial activities. The study confirms the relevance of the Technology Acceptance Model (TAM) and provides insights for policymakers and fintech developers in promoting efficient, secure, and inclusive digital financial services.